Metabolic syndrome is associated worsened erectile function in patients undergoing TURP due to benign prostatic hyperplasia. (9th April 2021) - Erkoc, Mustafa; Besiroglu, Huseyin; Otunctemur, Alper; Polat, Emre Can; Bozkurt, Muammer
Abstract: Introduction: Transurethral resection of the prostate (TURP) is the gold standard method for surgical treatment of benign prostatic hyperplasia (BPH). So, the complications of TURP is important, in which erectile dysfunction is the most important. The aim of the present study is to evaluate erectile dysfunction in patients undergoing TURP treatment for BPH and investigate the correlation between metabolic syndrome and erectile dysfunction. Materials and methods: This study included 120 patients who underwent surgery for BPH at Beylikdüzü State Hospital and Okmeydani Training and Research Hospital. IIEF-5 form was administered to the patients before the surgery and six months after the surgery. The Student's t -test, Wilcoxon, and chi-square test were used in the statistical analysis. Results: The patients were investigated by IIEF-5 scoring into three groups (severe, moderate, and non-ED (erectyl disfunction)-mild). The statistical analysis of IIEF-5 form administered to 120 patients who underwent surgery did not show any significant difference before surgery and six months after surgery ( p  > 0.05). Metabolic syndrome and erectile dysfunction correlation were examined, and a significant correlation was obtained between metabolic syndrome and severe erectile dysfunction ( p  < 0.05). Conclusions: IIEF-5 results administered before and after surgery showed no significant difference. The study showed that patients with metabolic syndrome have a higher probability of having erectile dysfunction after TURP compared to patients without metabolic syndrome. Moreover, post-surgery, patients with metabolic syndrome seemed to be affected negatively regarding erectile dysfunction compared to patients with no metabolic syndrome.